Application of Wischmeier-Smith, EPIC, M-USLE, and WEPP Methods for Determination of Erodibility Factor (K) of Soil - Brigitta Ery Septiyanti; Ngadisih Ngadisih; Chandra Setyawan; Sahid Susanto (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
The purpose of this study was to apply and to evaluate four methods (Wischmeier-Smith, EPIC, M-USLE, and WEPP) for calculating erodibility factor (K) of soil. The field measurement was carried out in a village laid on Southern Mountains of Java, where cocoa-based agrotourism is growing fast in the area. The land use of study area was captured by using drone. The soil samples were taken from land use of shrub, moors, and garden. Then, the samples were analyzed physical and chemical properties. This study obtained the K factor was in the range 0.12 to 0.22 for Wischmeir-Smith, 0.29 to 0.33 for EPIC, 10–3 to 3×10–4 for M-USLE, and 2×10–4 to 0.1 for WEPP. Based on literature (similar study and site, or soil type approach), the K factor obtained from Wischmeier-Smith method was in the range of reference. While other methods, the K factor was higher or lower than benchmark value.  The proposed method in this study could be applied to calculate K factors of soil. However, the M-USLE and WEPP methods still have shortcomings in the simulation process of erosion and surface run off rates to obtain the K factor.  Keywords: Agrotourism, Drone, Land use, Soil erosion